Analysis of Students’ Awareness Toward The Importance of Mastering English Skill for Their Future Career - Muchammad Sofyan Firmansyah (TRANSFORM: Journal of English Language Teaching and Learning, 2025)
This research investigates the awareness level of students in Politeknik Harapan Bersama regarding the importance of mastering English skills, specifically in the context of future career development. Using a structured questionnaire administered to 42 students from various departments, the results reveal a generally low level of awareness and motivation toward English language acquisition for professional advancement. Reliability and validity analyses were conducted, including Cronbach's alpha, item-total correlation, and p-value t-tests. The findings underline the urgent need for targeted interventions and curriculum reforms to enhance English proficiency and awareness among vocational learners.